2008
DOI: 10.1111/j.1440-1827.2008.02268.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CD68+ tumor‐associated macrophages in patients with diffuse large B‐cell lymphoma and its relation to prognosis

Abstract: Tumor-associated macrophages (TAM) have been ascribed both pro- and anti-tumor properties, but the majority of clinical cancer studies have shown that the presence of a high number of TAM is related to poor prognosis, suggesting that TAM predominantly exert pro-tumoral activity. The prognostic role of TAM in patients with diffuse large B-cell lymphoma (DLBCL), however, is so far unknown. Therefore, TAM were immunohistochemically stained with a CD68 antibody in a retrospective, population-based study including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 11 publications
4
59
0
2
Order By: Relevance
“…Whereas Nam et al 8 reported similar findings, as mentioned above, and the study by Cai et al 15 also showed that CD68 is a marker of poor outcome in CHOP-treated DLBCL patients, the studies by Hasselblom et al, 16 Meyer et al 17 and Coutinho et al 18 did not reveal significant associations between CD68 protein expression and survival. Furthermore, Wada et al 19 and Marchesi et al 20 reported that an M2 macrophage phenotype, as defined by double staining for CD68 and CD163, is associated with adverse outcome in R-CHOP-treated patients, whereas an M1 phenotype is not.…”
mentioning
confidence: 43%
“…Whereas Nam et al 8 reported similar findings, as mentioned above, and the study by Cai et al 15 also showed that CD68 is a marker of poor outcome in CHOP-treated DLBCL patients, the studies by Hasselblom et al, 16 Meyer et al 17 and Coutinho et al 18 did not reveal significant associations between CD68 protein expression and survival. Furthermore, Wada et al 19 and Marchesi et al 20 reported that an M2 macrophage phenotype, as defined by double staining for CD68 and CD163, is associated with adverse outcome in R-CHOP-treated patients, whereas an M1 phenotype is not.…”
mentioning
confidence: 43%
“…For example, while the gene signature of non-malignant cells in DLBCL indicates that a myeloidrich signature is a positive prognostic factor, 27 the total number of intra-tumor macrophages did not correlate with prognosis. 28 However, evaluation of macrophage phenotype indicated that M2 (CD163C) macrophage predict worse prognosis. 29 These studies highlight the heterogeneity of myeloid cell functions.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] IHC can be extended to clinical practice, which makes it highly attractive as a diagnostic and prognostic tool. Nevertheless, the results published regarding the immune microenvironment in DLBCL are contradictory.…”
Section: Introductionmentioning
confidence: 99%